2014
DOI: 10.4028/www.scientific.net/amm.660.125
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Mechanical Properties for 2D Woven Kenaf Composite

Abstract: Abstract:Woven composite based on natural fiber increasingly used for many applications in industries because of their advantages such as good relative mechanical properties and renewable resources, but there are some issues as cost and protracted development period to perform reliability evaluation by experimental with real scale. Predictive modeling technique is use to minimize the need for physical testing, shorten design timescales and provide optimized designs. Mechanical properties of woven fabrics for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 14 publications
(17 reference statements)
1
9
0
Order By: Relevance
“…The mechanical properties of woven kenaf composite depended on the crimp and porosity. [77] Woven banana and kenaf (40%) Polyester (PE)…”
Section: Kenaf Fabric Epoxymentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanical properties of woven kenaf composite depended on the crimp and porosity. [77] Woven banana and kenaf (40%) Polyester (PE)…”
Section: Kenaf Fabric Epoxymentioning
confidence: 99%
“…A yarn, consisting of either staple or filament fibre or other comparable forms and compounds come in different sizes and shapes, is relatively strong, and flexible. size, where the correct choice of yarn size is capable to provide optimum force value and strength to withstand the deformation of the woven fabric and the good mechanical properties of the composites [77]. In addition to the properties of matrix and yarn, the strength and hardness of woven fabric strengthened composites are determined by the structural parameters of materials, i.e., the fabrics counts and weave designs.…”
Section: Yarn Propertiesmentioning
confidence: 99%
“…For instance, Alavudeen et al [18] has found that the plain fabric of banana/kenaf reinforces polyester composite and shows improved tensile properties compare to the twill fabric weave design. A study by Wahab and co-workers [19] on woven composite have shown that the performance of woven kenaf composite are affected by yarn size and weave design that determine the woven fabric porosity and crimp percentage. These are the main factors that control the mechanical properties of the composite.…”
Section: Introductionmentioning
confidence: 99%
“…According to Jambari et al [26], hybridisation in composite area is a method of the combination of different resources and processes with different properties for the improvement of existing material. Several studies have been carried out on utilising kenaf yarn for fabric composite production [18,19,21,24,27]. The idea of hybrid weaving between synthetic fibres and kenaf fibres is highly recommended to compensate for the dramatic loss of strength.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Alavudeen et al [15] found that plain fabric made of banana/kenaf reinforced polyester composite showed improved tensile properties compared to the twill fabric weave design. A study by Wahab and co-workers [16] on woven composite revealed that the performance of woven kenaf composite were affected by yarn size and weave design that determine the woven fabric porosity and crimp percentage. These factors was found to be the main factor that control the mechanical properties of the composite.…”
Section: Introductionmentioning
confidence: 99%